Analisis Pengaruh Overload Pilihan terhadap Paralisis Keputusan dalam Industri Pemesanan Makanan Secara Daring - Kumala, Devi; Maizi, Zahrul (Jurnal Manajemen dan Teknologi, 2025)
The online food delivery industry has grown rapidly, providing convenience for consumers to choose meals. However, the increasing number of available options often leads to confusion and difficulty in making decisions. The phenomenon of choice overload, which occurs when too many options are offered, can lead to decision paralysis, where consumers struggle to choose or may not make a decision at all. This study aims to examine the impact of choice overload on decision paralysis in online food ordering and explore how demographic factors such as age and gender affect consumer experiences. A survey of 100 respondents was conducted, and the data were analyzed using regression analysis and independent sample t-tests. The results show that choice overload significantly affects decision paralysis, explaining about 28% of the variation in decision paralysis. Additionally, significant differences were found between younger and older age groups regarding this phenomenon, while gender did not influence decision-making. These findings provide a basis for food delivery platform managers to design applications with a simple interface and more curated options to reduce confusion and enhance the user experience in decision-making.